EFISIENSI INVESTASI, TATA KELOLA, DAN NILAI PERUSAHAAN: STUDI PADA SEKTOR MANUFAKTUR - Tampenawas, Jeremiah David Rianoto; Kusumadewi, Ni Luh Gde Lydia (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
The research focuses on analyzing the effect of investment efficiency, independent board of commissioners, and audit committees on the firm value of manufacturing firms listed on the Indonesia Stock Exchange in the periods 2020–2022. This research uses a purposive sampling method, choosing 23 manufacturing companies that published complete financial statements annually. We use Tobin's Q to measure firm value, ROA and sales growth residuals to capture investment efficiency, whereas independent commissioners and audit committees are assessed on the basis of proportions and frequency of meetings. The results show investment efficiency and independence commissioners have a positive effect on firm value. The audit committee has a significant effect. These findings add to the corporate governance literature and can facilitate investors during their decision-making by providing firm-level insights.